Proceedings of the 2019 Ramazzini Days: Session V - Work of the Fellows (Oral) - VV, AA (European Journal of Oncology and Environmental Health, 2019)
1. Mortality from silicosis in Brazil: Temporal trends in the period 1980-2017 Eduardo Algranti, Brazil 2.. Radiographic changes in Colombian asbestos factory workers Arthur Frank, USA 3. Severe silicosis outbreak in engineered stone fabrication workers - U.S. perspectives Robert Harrison, USA 4. The first announcement of establishing The Japan Association of Occupational Health Law Fujio Kayama, Japan 5. The triumph of doubt: Dark money and the science of deception David Michaels, USA 6. Potential role of Army Medical Forces in fighting cancer: An untapped resource Pier Giorgio Natali, Italy 7. Sibaté, Colombia: Another asbestos induced public-health crisis Juan Pablo Ramos-Bonilla, Columbia